A szubjektív jogvédelem korlátai az utakat érintő telekalakítási ügyekben (The limits of subjective legal protection in land reparcelling cases concerning roads) - Bettina Kozák (KözigazgatásTudomány)
The plot restructuring procedure is a special procedure that must satisfy both the real estate registration law and the construction law requirements. With regard to the need to maintain the regulatory lines, which are subject to construction law requirements, judicial practice over the last ten years or so has significantly softened the rule that the plot must be formed along the regulatory line, moving in the direction of subjective legal protection. The last ten years or so have also seen the development of a “bad practice” whereby the notarial authority did not, or at least not always require that the area designated as a public road in the local building regulations should actually be converted into a public road in the context of the plot restructuring procedure, but accepted it, even if the name of the property created after the plot restructuring became a private road not closed to public traffic. The situation was further aggravated by the fact that these plot restructurings were generally entered in the real estate registry without the private roads not closed to public traffic actually being built. The resulting illegitimate situation was also taken up with the building control authorities.